A Teleconsultation Device, Consult Station, for Remote Primary Care: Multisite Prospective Cohort Study - Géraldine Falgarone; Guilhem Bousquet; Arnaud Wilmet; Albert Brizio; Valérie Faure; Celestin Guillouet; Franck Baudino; Isabelle Roque; Samuel Mayol; Frederic Pamoukdjian (JMIR Publications, 2022)
BackgroundTelemedicine technology is a growing field, especially in the context of the COVID-19 pandemic. Consult Station (Health for Development) is the first telemedicine device enabling completely remote medical consultations, including the concurrent collection of clinical parameters and videos. ObjectiveOur aim was to collect data on the multisite urban and suburban implementation of the Consult Station for primary care and assess its contribution to health care pathways in areas with a low density of medical services. MethodsIn a proof-of-concept multisite prospective cohort study, 2134 consecutive patients had teleconsultations. Consultation characteristics were analyzed from both the patient and practitioner perspective. ResultsIn this study, the main users of Consult Station were younger women consulting for low-severity seasonal infections. Interestingly, hypertension, diabetes, and preventive medical consultations were almost absent, while they accounted for almost 50% of consultations with a general practitioner (GP). We showed that for all regions where the Consult Station was implemented, the number of consultations increased as GP density decreased. The study of practitioner characteristics showed GPs from metropolitan areas are motivated to work with this device remotely, with a high level of technology acceptability. ConclusionsThe multisite implementation of Consult Station booths is suitable for primary care and could also address the challenge of "medical deserts." In addition, further studies should be performed to evaluate the possible contribution of Consult Station booths to limiting work absenteeism.